2017
DOI: 10.1002/oby.21837
|View full text |Cite
|
Sign up to set email alerts
|

Skin in the game: Does paying for obesity treatment out of pocket lead to better outcomes compared to insurance coverage?

Abstract: Data from an academic medical weight management program suggest that individuals with access to insurance coverage for nonsurgical obesity treatment have lower levels of attrition and similar levels of participation and outcomes as those who pay out of pocket.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…We do acknowledge that the provision of total subsidy was also likely a key factor. In other studies, retention has been found to be low among commercial weight‐loss programmes and medically supervised weight loss when financial support is not provided . For example, retention was 22% at 6 months and only 7% at 12 months among Jenny Craig participants …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We do acknowledge that the provision of total subsidy was also likely a key factor. In other studies, retention has been found to be low among commercial weight‐loss programmes and medically supervised weight loss when financial support is not provided . For example, retention was 22% at 6 months and only 7% at 12 months among Jenny Craig participants …”
Section: Discussionmentioning
confidence: 95%
“…17 Details about Innergy have been published previously. 18,19 In the first 3 months, participants have weekly calls with their coach, and then calls decrease in occurrence after that point (once a month during months 4-12 and every 6-8 weeks in months [13][14][15][16][17][18][19][20][21][22][23][24]. The coaches provide support and promote behaviour change using motivational interviewing techniques-coaching is considered the key feature of this programme.…”
Section: Description Of Commercial Programmementioning
confidence: 99%
See 1 more Smart Citation